Revitalising traditional Malay woodcarving through design for sustainability - Shahrul Anuwar Mohamed Yusof
In the age of global industrialisation and mass production, traditional crafts offer an example of long-standing 'local' approaches to material culture that are often socially, environmentally and economically reifying. However, evidence suggests that traditional crafts struggle to survive, and this is also the case in Malaysia. Moreover, there has been limited academic investigation into the meaning and manifestation of sustainable development among craftspeople, and the relationship of this to traditional Malaysian heritage. The central aim of this thesis is to investigate the potential and provide an indepth understanding of the relationship between Malay craft and design for sustainability, focusing especially on traditional woodcarving. The key research question is; How can woodcarving, as a culturally significant craft practice, be revitalised in Malaysia through effective design contributions and in accordance with sustainable design principles? Data was collected via semi-structured interviews in Malaysia with 37 respondents from three groups of stakeholders in the craft industry: producers, supporters, and buyers; two case studies were also carried out in Malaysia. The relationships reviewed between various themes and sub-themes and organising them as a coherent whole constitutes an extensive qualitative study. Five main research findings are identified, which informed the development of a Craft Revitalisation Framework for Malay Traditional Woodcarving. This framework identifies key factors and their relationships that can inform context appropriate revitalisation strategies among the various stakeholders. The study recognises the need to involve appropriate stakeholders, including designers, in the development of such strategies. The conclusions from this study provide a better understanding on the significance, value and meaning of traditional Malay crafts, including woodcarving, in accordance with the principles of sustainability. In addition, it offers a useful tool and a well-founded direction to help ensure the future viability of craft practices.